Coping : essays on the practice of Government - Moynihan, Daniel P. (New York, 1973)
Daniel P. Moynihan, a leading political scientist, is one of the very few intellectuals in American history to have been so deeply involved with the practice of government. This collection of es says written during the years of this govern ment service reflects the knowledge and insight that Moynihan gained during this difficult period in America's history. The subjects of these challenging and original essays range from welfare to traffic safety, from political re form to the President's relationship with the press, from racial relations to education and urban affairs. Yet the essays all have a single theme: that to cope with specific public issues you must first define the nature of the problems involved. For Ambassador Moynihan the crucial step in solving public problems is, therefore, an intellectual one. He is concerned, in other words, with how the trained social scientist can con tribute to the practice of government.
Keywords: United states social conditions 1960